KETERANGAN AHLI DALAM SISTEM PERADILAN PIDANA ANAK - Akhmad Sultan Al-Ghajali Akbar (Badamai Law Journal, 2022)
Abtract: the results of the research can be concluded that: First, The Criteria of Experts in the Criminal Justice System of Children are: a. Bachelor's degree; b. Certificate/diploma; c. Certain positions; d. Advanced training in a particular field; e. Have a specific specialty; f. Recognition as a teacher, lecturer, or coach in a particular field; g. Professional License, if still valid; h. Participate as a membership in a professional organization; leadership positions in the organization are better; i. Publication of articles, books, or other publications, and can also be a reviewer. It would be one of the supporters that expert witnesses have long-term experience; j. Technical certification; k. Industry awards or recognition. Second, The strength of expert evidence in the child justice system is binding, namely that this provision is guided by the system or theory of proof based on the Law (Negatief Wetterlijk Bewijstheorie) must limit the prohibition to the judge to impose a criminal on a person who combines two elements, namely the provision of proof under the law and the element of the judge's belief into one element that is inseparable. The judge's conviction is considered none or nil if the conviction is not obtained from the evidence of expert information in the field of child psychology can also be called psychiatry.